Experimental Granulomatous Pulmonary Nocardiosis in BALB/C Mice - Larcombe, Alexander; Mifuji Lira, Roque Masaharu; Limón Flores, Alberto Yairh; Salinas Carmona, Mario César; Ortiz Stern, Alejandro (2016)
Pulmonary nocardiosis is a granulomatous disease with high mortality that affects both immunosuppressed and immunocompetent patients. The mechanisms leading to the establishment and progression of the infection are currently unknown. An animal model to study these mechanisms is sorely needed. We report the first in vivo model of granulomatous pulmonary nocardiosis that closely resembles human pathology. BALB/c mice infected intranasally with two different doses of GFP-expressing Nocardia brasiliensis ATCC700358 (NbGFP), develop weight loss and pulmonary granulomas. Mice infected with 109 CFUs progressed towards death within a week while mice infected with 108 CFUs died after five to six months. Histological examination of the lungs revealed that both the higher and lower doses of NbGFP induced granulomas with NbGFP clearly identifiable at the center of the lesions. Mice exposed to 108 CFUs and subsequently to 109 CFUs were not protected against disease severity but had less granulomas suggesting some degree of protection. Attempts to identify a cellular target for the infection were unsuccessful but we found that bacterial microcolonies in the suspension used to infect mice were responsible for the establishment of the disease. Small microcolonies of NbGFP, incompatible with nocardial doubling times starting from unicellular organisms, were identified in the lung as early as six hours after infection. Mice infected with highly purified unicellular preparations of NbGFP did not develop granulomas despite showing weight loss. Finally, intranasal delivery of nocardial microcolonies was enough for mice to develop granulomas with minimal weight loss. Taken together these results show that Nocardia brasiliensis microcolonies are both necessary and sufficient for the development of granulomatous pulmonary nocardiosis in mice.